Effects of Different Types of Pathogenic Variants on Phenotypes of Familial Hypercholesterolemia - Tada, Hayato; Kojima, Nobuko; Yamagami, Kan; Nomura, Akihiro; Nohara, Atsushi; Usui, Soichiro; Sakata, Kenji; Fujino, Noboru; Takamura, Masayuki; Kawashiri, Masa-Aki (Frontiers in Genetics, 2022)
Objective: It has been shown that pathogenic variants are associated with poor clinical outcomes in patients with familial hypercholesterolemia (FH). However, data on the effect of different types of pathogenic variants on FH phenotype is limited. Methods: We retrospectively investigated the associations between genotypes and phenotypes, including low-density lipoprotein (LDL) cholesterol level and the occurrence of major adverse cardiac events (MACEs), defined as cardiovascular death, myocardial infarction, unstable angina, or coronary artery revascularization, in patients with FH (N = 1050, male/female = 490/560). Based on genotype, the patients were divided into the following three groups: patients without pathogenic variants, patients with missense variants, and patients with protein-truncating variants (PTVs). Cox proportional hazard model was used to identify the factors associated with MACEs. Results: The median follow-up duration was 12.6 years (interquartile range = 9.5–17.9 years). There were 665 patients with FH-mutation (277 patients with missense variants and 388 patients with PTVs) and 385 patients without FH-mutation. Over the follow-up duration, 175 MACEs were observed. We identified 89 different pathogenic variants in the 665 patients with FH. LDL cholesterol level was found to be significantly higher in patients with PTVs (256 mg/dL) than in patients with missense variants (236 mg/dL) and patients without pathogenic variants (216 mg/dL). It was also found that PTVs and missense variants are significantly associated with MACEs (hazard ratio [HR] = 1.58, 95% confidence interval [CI] = 1.08–2.08, P = 0.0033 and HR = 3.24, 95% CI = 2.12–4.40, P = 3.9 × 10−6, respectively), independent of classical risk factors. Conclusion: Pathogenic variants, especially PTVs, are significantly associated with poor outcomes in patients with FH. Genetic testing is useful for the diagnosis and risk stratification of patients with FH.